2017
DOI: 10.3329/bjvm.v14i2.31386
|View full text |Cite
|
Sign up to set email alerts
|

Study on Bovine Sub-Clinical Mastitis on Farm Condition With Special Emphasis on Antibiogram of the Causative Bacteria

Abstract: The study was conducted to find out the prevalence of sub-clinical mastitis (SCM) and antibiogram of the causative bacteria in dairy cows at the Sylhet govt. Dairy Farm (SGDF) and Local Farms of Sylhet (LFS) during the period of July2014 to June2015. These farms were selected to assess the predominant types of bacteria involved in causing sub-clinical mastitis and to know the in vitro antibiotic sensitivity spectrum of these bacterial isolates against the commonly used antibiotics and to study the economic eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 4 publications
(4 reference statements)
2
2
0
Order By: Relevance
“…Isolates were highly resistant to penicillin (100%), cefpodoxime (70%), ofloxacin (68.1%), and ciprofloxacin (61.1%). The sensitivity findings of this study are in agreement with previous reports [ 35 , 36 , 37 ]. The reports on isolate resistance to ciprofloxacin, ofloxacin, cefpodoxime, and penicillin are in agreement with previous findings [ 38 , 39 , 40 , 41 , 42 ].…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…Isolates were highly resistant to penicillin (100%), cefpodoxime (70%), ofloxacin (68.1%), and ciprofloxacin (61.1%). The sensitivity findings of this study are in agreement with previous reports [ 35 , 36 , 37 ]. The reports on isolate resistance to ciprofloxacin, ofloxacin, cefpodoxime, and penicillin are in agreement with previous findings [ 38 , 39 , 40 , 41 , 42 ].…”
Section: Resultssupporting
confidence: 94%
“…The highest resistance was shown by isolates of E. coli to penicillin (100%) and cefpodoxime (73.3%). Similar sensitivity findings of E. coli to doxycycline hydrochloride, ciprofloxacin, gentamicin, tetracycline, and ofloxacin are in agreement with previous reports [ 35 , 36 , 37 ]. In the present study, the highest resistance was shown by E. coli isolates to penicillin (100%), followed by cefpodoxime (73.3%).…”
Section: Resultssupporting
confidence: 93%
“…However, the prevalence of the major streptococci was variable based on geographical locations ( 4 ). In Bangladesh, information on Streptococcus and their antibiotic susceptibility in mastitis are minimal ( 14–16 ), and to the best of our knowledge, no research has been documented on the occurrence, diversity and molecular characteristics of Streptococcus in clinical mastitis of cattle in Bangladesh. In Bangladesh, dairying is a growing industry and mostly dominated by small holding farms producing 70-80% of the country’s total milk ( 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…Mastitis is an inflammatory condition of the mammary glands characterized by chemical, bacteriological and physical changes in milk or udder (Nazifi et al, 2011). There are three main classes of mastitis: clinical mastitis (CM), sub-clinical mastitis (SCM) and chronic mastitis (ChM) (Islam et al, 2017). In clinical mastitis, there are changes in milk quality i.e.…”
Section: Introductionmentioning
confidence: 99%